Potential value of pharmacological agents acting on toll-like receptor (TLR) 7 and/or TLR8 in COVID-19 - Amani E. Khalifa, PhD (Elsevier, 2021)
The COVID-19 pandemic is an ongoing global pandemic of coronavirus disease 2019 as an atypical type of viral pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Many potential pharmacotherapies are currently being investigated against this disease. This article points to and justifies, the importance of investigating the potential therapeutic value of pharmacological agents acting on Toll-like Receptor (TLR) 7 and/or TLR8 as double-edged swords combating COVID-19. Induction of TLR7 and/or TLR8 may be investigated as a strategy to stimulate immunity and may be added to anti-COVID19 vaccines to cope with their current viral escape challenge. TLR7 stimulation may not only help viral clearance through Th1 antiviral responses but may also provide beneficial broncho- and vaso-dilatory, as well as, anti-inflammatory effects. Pharmacological compounds acting as TLR7 and/or TLR8 agonists may be of value if used by frontline healthcare workers with comorbidities who demonstrate mild symptoms of the disease. On the other hand, TLR7 and/or TLR8 antagonists may be used in combination with immune-modulatory/anti-inflammatory drugs in severe cases of the disease, with potential synergistic effects that could also help in reducing the doses of such therapies, and consequently their adverse effects.